A HISTORICAL UPDATE ON HANDBALL GAME EVOLUTION THROUGHOUT XXTH CENTURY - Juan de Dios Román Seco (Federación Extremeña de Balonmano; University of Extremadura, 2015)
The evolution of sport is subject to continuous review and revision of historical events from a detailed analysis of the elements of the game. The aim of this study was to perform an update of others papers published in E-balonmano.com journal about the game evolution in handball. Modern sport has evolved and is evolving quickly in line with the demands of the show and handball has not been left out of it. The professionalization has been a way to improve the game characteristics for the show. Specialists and managers of the elite, as well as those who are new to the knowledge of the game, should not forget the roots, the foundations and the historical evolution of attacking play in this sport specialty. If supported in handball roots, bringing creative ideas will enrich this dynamic, competitive and intelligent product that draws the Handball possible.